Alignment and mismatch in role relations at end-of-life: A constructivist grounded theory study. Issue 5 (28th May 2021) - Lowrie, Daniel; Ray, Robin; Plummer, David; Yau, Matthew
Abstract: In this Australian, constructivist grounded theory study, we undertook in-depth interviews with 11 dying people and 8 caregivers to examine their perspectives on role relations at end-of-life. We found that situations of role alignment between dying people and their family and friends support positive relational and practical outcomes, whereas role mismatch can cause considerable distress. Factors contributing to role mismatch at end-of-life were: dying people and their caregivers' efforts to shield each other from emotional harm; fear of social exclusion; and unwanted focus on the dying identity. Our findings highlight a need for flexibility and adaptability in end-of-life role relations.